SUBGRUP -NORMAL DAN SUBRING -MAX - Kristi Utomo Kristi Utomo (MATEMATIKA FSM, UNDIP, 2016)
ABSTRACT. For any group , subgroup of is called -normal subgroup if there exist a normal subgroup of such that and where is maximal normal subgroup of which is contained in . On the other side, for each ring , subring of is called -max subring if there exist an ideal of such that and where is maximal ideal of which is contained in . Subgroup normal of is -normal subgroup if and only if is maximal normal subgroup and ideal of is -max subring if and only if is maximal ideal. Every group and ring is -normal subgroup and -max subring of itself.